Electrolyte additive, non-aqueous electrolyte and battery

By using electrolyte additives of silicanitrile compounds and trithiophosphite compounds in lithium-rich manganese-based batteries, a stable interface film is formed, which solves the problems of poor battery cycle life under high charging voltage and serious battery gas production, and significantly improves the cycle life and safety of the battery.

CN119650854APending Publication Date: 2025-03-18TIANMU LAKE INST OF ADVANCED ENERGY STORAGE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411822053.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Lithium-rich manganese-based batteries have poor cycle life under high charging voltage and severe gas production in the battery cell, which poses safety hazards.

Method used

Electrolyte additives including silicanitrile compounds and trithiophosphite compounds are used to form a stable interface film on the surface of the positive and negative electrode materials through these additives, which improves the stability of the film and lithium ion conduction performance, inhibits the dissolution of manganese ions and the formation of highly reactive oxygen species.

Benefits of technology

It significantly improves the cycle life of the battery cell, reduces the gas production phenomenon of the battery cell, reduces safety risks, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650854A_ABST
    Figure CN119650854A_ABST
Patent Text Reader

Abstract

The invention relates to an electrolyte additive, a non-aqueous electrolyte and a battery, belongs to the technical field of lithium ion batteries, and is used for solving at least one of the problems of poor cycle life, serious gas production of a battery cell and the like of an existing lithium-rich manganese-based battery under relatively high charging voltage. The electrolyte additive comprises a silicon nitrile compound and a trithio phosphite compound, the additive forms a CEI / SEI film on the surface of a positive electrode material and the surface of a negative electrode material prior to a solvent under the high voltage (larger than or equal to 4.5 V), Si, P and S remarkably improve the stability and lithium ion conducting performance of the interface film, therefore, oxidation-reduction decomposition of the electrolyte is effectively inhibited, and the service life of the electrolyte is prolonged. The battery cell cycle life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an electrolyte additive, a non-aqueous electrolyte and a battery. Background Art

[0002] In recent years, lithium-rich manganese-based cathode materials have attracted the attention of researchers due to their high specific capacity. However, lithium-rich manganese-based cathode materials require a higher charging voltage (≥4.5V) to exert their high capacity advantage, and the anions in the material undergo redox reactions to produce highly oxidized reactive oxygen species or free radicals. The combined effect of these two factors (high voltage and highly reactive oxygen species) significantly increases electrolyte side reactions, resulting in severe gas production in the battery system, poor cycle life, and safety hazards. Summary of the invention

[0003] In view of the above analysis, the present invention aims to provide an electrolyte additive, a non-aqueous electrolyte and a battery to solve at least one of the problems of existing lithium-rich manganese-based batteries, such as poor cycle life at a higher charging voltage and severe gas production of the battery cells.

[0004] In a first aspect, the present invention provides an electrolyte additive, wherein the additive comprises a silicon nitrile compound shown in structural formula I and a trithiophosphite compound shown in structural formula II;

[0005]

[0006] Wherein, R is selected from at least one of trimethylsilyl, trimethylsilyloxy, C1-C10 unsubstituted or substituted alkyl, alkoxy, C2-C10 unsubstituted or substituted alkenyl, C2-C10 unsubstituted or substituted alkynyl, and C6-C10 unsubstituted or substituted aryl;

[0007] R1 to R6 are independently selected from at least one of trimethylsilyl, trimethylsilyloxy, C1 to C10 unsubstituted or substituted alkyl or alkoxy, C2 to C10 unsubstituted or substituted alkenyl, C2 to C10 unsubstituted or substituted alkynyl, C6-C10 unsubstituted or substituted aryl, hydrogen, halogen, cyano, isocyanate, and isothiocyanate.

[0008] Furthermore, R is at least one of a C1-C10 unsubstituted or substituted alkyl group, an alkoxy group, and a C2-C10 unsubstituted or substituted alkenyl group, and R1-R6 are independently selected from at least one of a C1-C10 unsubstituted or substituted alkyl group, an isocyanate group, and a trimethylsilyl group.

[0009] Furthermore, the structural formula I is selected from at least one of structural formulas I-1 to I-3:

[0010]

[0011] Furthermore, the structural formula II is selected from at least one of structural formulas II-1 to II-3:

[0012]

[0013] In a second aspect, the present invention provides a non-aqueous electrolyte comprising the above-mentioned electrolyte additive.

[0014] Furthermore, the non-aqueous electrolyte also includes an organic solvent, a lithium salt and conventional additives.

[0015] Furthermore, the total mass of the electrolyte additive and the conventional additive is 5-20% of the total mass of the non-aqueous electrolyte.

[0016] Furthermore, the mass of the silicon nitrile compound is 0.2-3% of the total mass of the non-aqueous electrolyte, and the mass of the trithiophosphite compound is 0.2-5% of the total mass of the non-aqueous electrolyte.

[0017] In a third aspect, the present invention provides a lithium-ion battery comprising the above-mentioned non-aqueous electrolyte.

[0018] Furthermore, the lithium-ion battery also includes a positive electrode, a negative electrode and a separator, and the active material in the positive electrode is a lithium-rich manganese-based active material.

[0019] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0020] (1) The electrolyte additives described in the present invention include silica nitrile compounds and trithiophosphite compounds. Under high voltage (≥4.5V), the structure of lithium-rich manganese-based positive electrode materials is unstable, the dissolution of manganese ions is aggravated, and highly active oxygen species are generated. The electrolyte additives described in the present invention include silica nitrile compounds and trithiophosphite compounds. The additives form CEI / SEI films on the surfaces of positive and negative electrode materials before the solvent. Among them, Si, P and S significantly improve the stability of the interface film and the lithium ion conductivity, thereby slowing down the occurrence of electrolyte-electrode interface side reactions; in addition, the cyanide group in the silica nitrile compound is preferentially adsorbed on the surface of the positive electrode material, and effectively inhibits the dissolution of manganese ions by forming a stable complex with manganese ions; P in the trithiophosphite compound is low-valent phosphorus, and S contains lone pairs of electrons, which can react with highly active oxygen species / free radicals in the positive electrode or form a bond with high-valent metal ions in the positive electrode material, effectively reducing the oxidation activity on the surface of the positive electrode material, thereby effectively improving the gas generation problem of the battery cell and significantly improving the cycle life of the battery cell;

[0021] (2) The cyano group in the silicon nitrile compound of the present invention is preferentially adsorbed on the surface of the positive electrode material, occupying the metal active sites on the surface of the positive electrode material, and the cyano group has a strong coordination ability, which can form a stable complex with the positive electrode metal ions, effectively inhibiting the dissolution of the positive electrode metal ions; the P in -PS in the trithiophosphite compound is low-valent phosphorus, which can capture highly active oxygen species / free radicals in the positive electrode; at the same time, the S in -PS contains lone pairs of electrons, which can form a bond with high-valent metal ions in the positive electrode material, thereby effectively reducing the oxidation activity on the surface of the positive electrode material;

[0022] (3) The two additives in the present invention are used in combination, and their synergistic effect can fundamentally inhibit the influence of two unfavorable factors, high voltage (≥4.5V) and highly active species, reduce the occurrence of electrolyte side reactions, and reduce the dissolution of positive electrode metal ions, thereby effectively inhibiting the gas production of the battery cell and improving the long cycle life.

[0023] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0025] Figure 1 This is a dissolution diagram of Mn ions in the positive electrode of a lithium ion battery made using the electrolyte of Comparative Example 3 of the present invention;

[0026] Figure 2 This is a dissolution diagram of Mn ions in the positive electrode of a lithium-ion battery made using the electrolyte of Example 1 of the present invention. DETAILED DESCRIPTION

[0027] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0028] A specific embodiment of the present invention discloses an electrolyte additive, wherein the additive comprises a silicon nitrile compound shown in structural formula I and a trithiophosphite compound shown in structural formula II;

[0029]

[0030] Wherein, R is selected from at least one of trimethylsilyl, trimethylsilyloxy, C1-C10 unsubstituted or substituted alkyl, alkoxy, C2-C10 unsubstituted or substituted alkenyl, C2-C10 unsubstituted or substituted alkynyl, and C6-C10 unsubstituted or substituted aryl;

[0031] R1 to R6 are independently selected from at least one of trimethylsilyl, trimethylsilyloxy, C1 to C10 unsubstituted or substituted alkyl or alkoxy, C2 to C10 unsubstituted or substituted alkenyl, C2 to C10 unsubstituted or substituted alkynyl, C6-C10 unsubstituted or substituted aryl, hydrogen, halogen, cyano, isocyanate, and isothiocyanate.

[0032] The electrolyte additives described in the present invention include silica nitrile compounds and trithiophosphite compounds. Under high voltage (≥4.5V), the structure of lithium-rich manganese-based positive electrode materials is unstable, the dissolution of manganese ions is aggravated, and highly active oxygen species are generated. The electrolyte additives described in the present invention include silica nitrile compounds and trithiophosphite compounds. The additives form CEI / SEI films on the surfaces of positive and negative electrode materials before the solvent, wherein Si, P and S significantly improve the stability of the interface film and the lithium ion conductivity, thereby slowing down the occurrence of electrolyte-electrode interface side reactions; in addition, the cyano group in the silica nitrile compound is preferentially adsorbed on the surface of the positive electrode material, and effectively inhibits the dissolution of manganese ions by forming a stable complex with manganese ions; P in the trithiophosphite compound is low-valent phosphorus, and S contains lone pairs of electrons, which can react with highly active oxygen species / free radicals of the positive electrode or bond with high-valent metal ions in the positive electrode material, effectively reducing the oxidation activity on the surface of the positive electrode material, thereby effectively improving the gas generation problem of the battery cell and significantly improving the cycle life of the battery cell. In addition, the cyano group in the silicon nitrile compound of the present invention is preferentially adsorbed on the surface of the positive electrode material, occupying the metal active sites on the surface of the positive electrode material, and the cyano group has a strong coordination ability, which can form a stable complex with the positive electrode metal ions, effectively inhibiting the dissolution of the positive electrode metal ions; the P in -PS in the trithiophosphite compound is low-valent phosphorus, which can capture highly active oxygen species / free radicals at the positive electrode; at the same time, the S in -PS contains lone pairs of electrons, which can bond with high-valent metal ions in the positive electrode material, thereby effectively reducing the oxidation activity on the surface of the positive electrode material.

[0033] The two additives in the present invention are used in combination, and their synergistic effect can fundamentally inhibit the influence of the two adverse factors of high voltage and high active species, reduce the occurrence of electrolyte side reactions, and reduce the dissolution of positive electrode metal ions, thereby effectively inhibiting the gas production of the battery cell and improving the long cycle life.

[0034] Preferably, R is at least one of C1-C10 unsubstituted or substituted alkyl, alkoxy, and C2-C10 unsubstituted or substituted alkenyl, and R1-R6 are independently selected from at least one of C1-C10 unsubstituted or substituted alkyl, isocyanate, and trimethylsilyl.

[0035] In a specific embodiment, the structural formula I is selected from at least one of structural formulas I-1 to I-3:

[0036]

[0037] It should be noted that compound I-2 can significantly improve the room temperature cycle performance of lithium-ion batteries, because compound I-2 contains two cyano groups, which has a better complex protection effect on the positive electrode metal ions, and the interface film generated by the -CF3 group is rich in LiF, which is conducive to the uniform deposition of lithium ions and further improves the stability of the interface film.

[0038] In a specific embodiment, the structural formula II is selected from at least one of structural formulas II-1 to II-3:

[0039]

[0040]

[0041] It should be noted that compound II-2 and compound II-3 have more obvious effects on circulation and gas production improvement. This is because the role of -CF3 and trimethylsilyl makes the interface film contain more LiF and silicate, which are beneficial to the transmission of lithium ions. All compounds in the present invention are existing or prepared by existing methods.

[0042] Another specific embodiment of the present invention discloses a non-aqueous electrolyte, including the above-mentioned electrolyte additive.

[0043] Specifically, the non-aqueous electrolyte further includes an organic solvent, a lithium salt and conventional additives.

[0044] In a specific embodiment, the total mass of the electrolyte additive and the conventional additive is 5-20% of the total mass of the non-aqueous electrolyte, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%.

[0045] Preferably, the mass of the silicon nitrile compound is 0.2-3% of the total mass of the non-aqueous electrolyte, for example, 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, and the mass of the trithiophosphite compound is 0.2% to 3% of the total mass of the non-aqueous electrolyte. 0.2-5% of the amount, for example, 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0%.

[0046] More preferably, the mass of the silicon nitrile compound is 0.5-1% of the total mass of the non-aqueous electrolyte, and the mass of the trithiophosphite compound is 0.5-2% of the total mass of the non-aqueous electrolyte.

[0047] In a specific embodiment, the mass of the organic solvent accounts for 60-85% of the total mass of the electrolyte, for example, 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 85%.

[0048] When the solvent content is low, the electrolyte conductivity is low, which is not conducive to ion transmission; when the solvent content is too high, the corresponding lithium salt and functional additive content is low, which also has a certain negative impact on battery performance.

[0049] In a specific embodiment, the mass of the lithium salt accounts for 10-20% of the total mass of the electrolyte, for example, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%. If the lithium salt content is too low or too high, it will have a relatively large impact on the viscosity and conductivity of the electrolyte, affecting the transmission of lithium ions, which is not conducive to the performance of lithium-ion batteries.

[0050] In a specific embodiment, the organic solvent includes any one or a combination of two or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl trifluoroethyl carbonate (FEMC), fluoroethylene carbonate (FEC), diethyl carbonate (DEC), propyl propionate (PP), ethyl propionate (EP), methyl propionate (MP), propyl acetate (PA), ethyl acetate (EA), ethyl butyrate (EB), γ-butyrolactone (GBL), γ-valerolactone (GVL), and δ-valerolactone (DVL).

[0051] Preferably, the organic solvent includes at least three of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC).

[0052] In a specific embodiment, the lithium salt includes any one or a combination of two or more of lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiODFB), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(oxalatoborate) (LiBOB), lithium hexafluoroantimonate (LiSbF6), lithium hexafluoroarsenate (LiAsF6), lithium difluorooxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0053] Preferably, the lithium salt includes at least two of LiPF6, LiPO2F2, LiBOB and LiODFB.

[0054] In a specific embodiment, the conventional additives include any one or a combination of two or more of 1,3-propane sultone (PS), 1,3-sultone (PST), 1,4-butane sultone (BS), vinyl sulfate (DTD), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), tris(trimethylsilyl) borate (TMSB), tris(trimethylsilyl) phosphate (TMSP), adiponitrile (ADN), succinonitrile (SN), ethylene glycol dipropylene glycol ether (DENE), 1,3,6-hexanetrinitrile (HTCN), succinic anhydride (SA), maleic anhydride (MA), citraconic anhydride (CTA) and methylene methane disulfonate (MMDS).

[0055] Another specific embodiment of the present invention discloses a lithium-ion battery, comprising the above-mentioned non-aqueous electrolyte.

[0056] Specifically, the lithium-ion battery further includes a positive electrode, a negative electrode and a separator.

[0057] Specifically, the active material in the positive electrode is a lithium-rich manganese-based active material.

[0058] Specifically, the active material in the negative electrode is one or more of natural graphite, artificial graphite, and silicon-carbon composite material.

[0059] The technical solution of the present invention is further explained below in conjunction with specific embodiments.

[0060] Example 1

[0061] An electrolyte of the present embodiment includes, by mass percentage, 1% of compound I-1, 2% of compound II-1, 1% of PS, 13.5% of LiPF6, 0.5% of LiPO2F2, and the rest is an organic solvent, wherein the organic solvent is propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and fluoroethylene carbonate (FEC), which are mixed in a mass ratio of PC:DEC:EMC:FEC=1:1:6:2.

[0062] The electrolyte of this embodiment is prepared by the following method: first, the organic solvent is mixed evenly, and then LiPF6 and LiPO2F2 are added in sequence. After they are fully dissolved, PS, compound I-1, and compound II-1 are added and fully dissolved for use.

[0063] Example 2

[0064] The electrolyte raw material and preparation method of this embodiment are the same as those of Example 1, except that the mass fraction of compound I-1 is 0.5%, and the total amount is kept unchanged by changing the amount of solvent added.

[0065] Example 3

[0066] The electrolyte raw material and preparation method of this embodiment are the same as those of Example 1, except that the mass fraction of compound I-1 is 0.2%, and the total amount is kept unchanged by changing the amount of solvent added.

[0067] Example 4

[0068] The electrolyte raw material and preparation method of this embodiment are the same as those of Example 1, except that the mass fraction of compound I-1 is 3%, and the total amount is kept unchanged by changing the amount of solvent added.

[0069] Example 5

[0070] The electrolyte raw material and preparation method of this embodiment are the same as those of Example 1, except that the mass fraction of compound II-1 is 0.5%, and the total amount is kept unchanged by changing the amount of solvent added.

[0071] Example 6

[0072] The electrolyte raw material and preparation method of this embodiment are the same as those of Example 1, except that the mass fraction of compound II-1 is 0.2%, and the total amount is kept unchanged by changing the amount of solvent added.

[0073] Example 7

[0074] The electrolyte raw materials and preparation method of this embodiment are the same as those of Example 1, except that the mass fraction of compound II-1 is 5%, and the total amount is kept unchanged by changing the amount of solvent added.

[0075] Example 8

[0076] The electrolyte raw material and preparation method of this embodiment are the same as those of Example 1, except that compound I-1 is replaced by compound I-2.

[0077] Example 9

[0078] The electrolyte raw material and preparation method of this embodiment are the same as those of Example 1, except that compound I-1 is replaced by compound I-3.

[0079] Example 10

[0080] The electrolyte raw material and preparation method of this embodiment are the same as those of Example 1, except that compound II-1 is replaced by compound II-2.

[0081] Embodiment 11

[0082] The raw materials and preparation method of an electrolyte in this comparative example are the same as those in Example 1, except that compound II-1 is replaced by compound II-3.

[0083] Comparative Example 1

[0084] The raw materials and preparation method of an electrolyte in this comparative example are the same as those in Example 1, except that compound I-1 is not added, and the total amount is kept unchanged by changing the amount of solvent added.

[0085] Comparative Example 2

[0086] The raw materials and preparation method of an electrolyte in this comparative example are the same as those in Example 1, except that compound II-1 is not added.

[0087] Comparative Example 3

[0088] The raw materials and preparation method of an electrolyte in this comparative example are the same as those in Example 1, except that compound I-1 and compound II-1 are not added.

[0089] Comparative Example 4

[0090] The raw materials and preparation method of an electrolyte in this comparative example are the same as those in Example 1, except that the addition amount of compound I-1 is 0.05%, and the total amount is kept unchanged by changing the addition amount of the solvent.

[0091] Comparative Example 5

[0092] The raw materials and preparation method of an electrolyte in this comparative example are the same as those in Example 1, except that the addition amount of compound I-1 is 4%, and the total amount is kept unchanged by changing the addition amount of the solvent.

[0093] Comparative Example 6

[0094] The raw materials and preparation method of an electrolyte in this comparative example are the same as those in Example 1, except that the addition amount of compound II-1 is 0.05%, and the total amount is kept unchanged by changing the addition amount of the solvent.

[0095] Comparative Example 7

[0096] The raw materials and preparation method of an electrolyte in this comparative example are the same as those in Example 1, except that the addition amount of compound II-1 is 6%, and the total amount is kept unchanged by changing the addition amount of the solvent.

[0097] Comparative Example 8

[0098] The raw materials and preparation method of an electrolyte in this comparative example are the same as those in Example 1, except that compound I-1 replaces succinonitrile (SN).

[0099] Comparative Example 9

[0100] The raw materials and preparation method of an electrolyte in this comparative example are the same as those in Example 1, except that compound I-1 is replaced by methoxytrimethylsilane, and the structural formula is as follows:

[0101]

[0102] Comparative Example 10

[0103] The raw materials and preparation method of an electrolyte in this comparative example are the same as those in Example 1, except that compound II-1 is replaced by triethyl phosphite, and the structural formula is as follows:

[0104]

[0105] Comparative Example 11

[0106] The raw materials and preparation method of an electrolyte in this comparative example are the same as those in Example 1, except that compound II-1 is replaced by triethylthiomethane, and the structural formula is as follows:

[0107]

[0108] Application Example 1 Lithium-ion Battery

[0109] (1) The electrolytes used were those of Examples 1-11 and Comparative Examples 1-11.

[0110] (2) Preparation of positive electrode:

[0111] The lithium-rich manganese-based positive electrode active material (OLO), conductive carbon black (Super-P), carbon nanotubes (CNT) and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96:1.5:0.5:2, and then dispersed in N-methyl-2-pyrrolidone (NMP), and stirred thoroughly to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on the positive electrode current collector Al foil, and after drying, it is rolled and die-cut to obtain a positive electrode sheet that meets the requirements.

[0112] (3) Preparation of negative electrode:

[0113] The negative electrode active materials graphite, silicon carbon, conductive carbon black (Super-P), binder styrene butadiene rubber (SBR), polyacrylic acid (PAA) and thickener carboxymethyl cellulose (CMC) are mixed in a mass ratio of 63:31.5:1.2:2:1.8:0.5, and then dispersed in deionized water to obtain a negative electrode slurry. The negative electrode slurry is evenly coated on the negative electrode current collector Cu foil, and after drying, it is rolled and die-cut to obtain a negative electrode sheet that meets the requirements.

[0114] (4) Preparation of lithium-ion batteries:

[0115] The positive and negative electrode sheets and the separator (PE / Al2O3 / PVDF(9+3+1+1)) prepared by the above method are stacked in order, wherein the separator is located in the middle of the positive and negative electrode sheets; the stacked battery cells are fixed with tape, and then packaged after cold pressing to form lithium-ion batteries with a thickness of 4.6 mm, a length of 85 mm, and a width of 50 mm; the battery cells are vacuum-baked at 80°C for 24 h to obtain battery cells to be injected with liquid; in a glove box with a dew point controlled below -40°C, the prepared electrolytes are injected into the battery cells respectively, and after standing at high temperature for 24 h and standing at room temperature for 12 h, formation, secondary sealing and capacity separation are carried out to complete the battery production.

[0116] First, lithium-ion battery performance test

[0117] The performance of the batteries prepared using the electrolytes of Examples 1-11 and Comparative Examples 1-11 were tested respectively, and the specific testing methods are as follows:

[0118] Cyclic performance test: At 25°C, charge to 4.50V at 0.33C constant current and constant voltage, cut-off current 0.05C, then discharge to 1.5V at 0.33C constant current, record the initial discharge capacity as C0, and test the initial thickness of the battery cell T0, repeat the charge and discharge 300 times, record the discharge capacity of the 300th week as C1, the battery cell thickness as T1, and calculate the capacity retention rate and battery cell thickness expansion rate of room temperature cycle according to the following formula: capacity retention rate = C1 / C0*100%, battery cell thickness expansion rate = (T1-T0) / T10*100%. The test results are shown in Table 1.

[0119] Table 1

[0120]

[0121] From Table 1, Comparative Examples 1-7 and Examples 1-11, it can be seen that adding silicon nitrile additives and trithiophosphite additives to the electrolyte is beneficial to improving the normal temperature cycle life of lithium-ion batteries and effectively inhibiting the gas production of the battery cells. The combined use of silicon nitrile additives and trithiophosphite additives is more effective in improving the cycle and inhibiting the gas production than when used alone. This is because when the two are used together, the positive and negative electrode materials are more fully protected, especially on the positive electrode material side, which reduces the impact of the two unfavorable factors of high voltage and active oxygen species, effectively slowing down the occurrence of side reactions at the electrode-electrolyte interface, thereby inhibiting the gas production of the battery cell and improving the cycle life of the battery cell.

[0122] It can be seen from Comparative Examples 1-7 and Examples 1-11 that the addition amount of silicon nitrile additives and trithiophosphite additives within the scope of the present invention can significantly improve the cycle life and gas production of the battery. Among them, it can be seen from Examples 1 to 4 that the more silicon nitrile additives are added, the more significantly the battery cycle capacity retention rate is improved. When the addition amount continues to increase, the battery cell impedance increases, resulting in a decrease in the battery cycle capacity retention rate, but the gas production inhibition effect is more obvious. Preferably, the addition amount of silicon nitrile compounds is 0.5-1%.

[0123] It can be seen from Examples 1 and 5 to 7 that the more the amount of trithiophosphite additive added, the more obvious the effect of improving the battery cycle performance. When the amount added continues to increase, the film is thicker and too dense, resulting in increased impedance, which is not conducive to the insertion and extraction of lithium ions, and the effect of improving the battery cycle performance is slightly deteriorated. Preferably, the amount of trithiophosphite compound added is 0.5-2%.

[0124] It can be seen from Comparative Example 4, Comparative Example 6, and Example 1 that when the amount of silicon nitrile additives or trithiophosphite additives added is too small, the film formation stability at the electrode-electrolyte interface is poor, and the positive electrode active oxide cannot be completely captured, and the protection effect is not obvious, resulting in poor battery cycle performance and serious gas production;

[0125] It can be seen from Comparative Example 5, Comparative Example 7 and Example 1 that when too much silicon nitrile additive or trithiophosphite additive is added, the impedance of the battery cell will be too large, which is not conducive to the transmission of lithium ions, and the battery cycle performance is not further improved, but the cost of the electrolyte is increased.

[0126] It can be seen from Comparative Example 1, Examples 1, 8, and 9 that adding silicon nitrile additives shown in structural formulas I-2 and I-3 to the electrolyte can also improve the room temperature cycle performance of lithium-ion batteries, and the improvement effect is more obvious. Because compound I-2 contains two cyano groups, it has a better complex protection effect on positive electrode metal ions, and the interface film generated by the action of the -CF3 group is rich in LiF, which is conducive to the uniform deposition of lithium ions and further improves the stability of the interface film. The -NCO group in compound I-3 has the effect of removing water and acid, which can eliminate the adverse effects of HF to a certain extent, improve the cycle performance and reduce the gas production of the battery core.

[0127] It can be seen from Comparative Example 2, Examples 1, 10, and 11 that adding compounds II-2 and II-3 to the electrolyte has a more obvious effect on improving circulation and gas production. This is due to the role of -CF3 and trimethylsilyl. When II-2 and II-3 additives are used, the interface film contains more LiF and silicate, respectively, which are beneficial to the transmission of lithium ions.

[0128] It can be seen from Comparative Examples 1, 8 to 9, and Example 1 that the addition of additives containing only cyano or only silicon has a slight improvement effect on the cycle performance, but the improvement effect is significantly worse than that of Compound I-1. This is because although the cyano group can inhibit the dissolution of positive electrode metal ions and reduce the occurrence of positive electrode interface side reactions, it significantly increases the impedance of the battery cell, which is not conducive to improving the normal temperature cycle performance of the battery cell. In addition, although additives containing only silicon can protect the positive electrode material through film-forming action, they have limited effect on inhibiting the dissolution of positive electrode metal ions. When the additive contains both cyano and silicon, it can have a dual inhibitory effect on the dissolution of positive electrode metal ions, and is beneficial to reducing the overall impedance of the battery cell.

[0129] Cyano groups generally protect positive electrode materials through complexation, and have poor compatibility with negative electrodes. In addition, cyano groups have large impedance. When cyano-containing nitrile additives are used alone, when the amount added is too much, the room temperature cycle performance will deteriorate. In addition to the role of cyano groups, silicon nitrile additives also participate in the formation of positive and negative electrode interface films, and have a certain protective effect on both positive and negative electrode materials. The film components are rich in silicates, have good stability and ionic conductivity, and thus effectively improve the cycle performance.

[0130] From Comparative Examples 2, 10-11, and Example 1, it can be seen that the addition of additives containing only P or S has a slight improvement effect on the cycle performance, but the improvement effect is significantly worse than that of Compound II-1. This is because the P of -PS in Compound II-1 is low-valent phosphorus, which can capture highly active oxygen species / free radicals in the positive electrode; at the same time, the S in -PS contains lone pairs of electrons, which can bond with high-valent metal ions in the positive electrode material, thereby effectively reducing the oxidation activity on the surface of the positive electrode material. Moreover, the interface film formed by Compound II-1 contains both P and S, and has better stability and conductivity.

[0131] Second, lithium-ion battery EDS test

[0132] The lithium-ion battery prepared by using the electrolyte of Comparative Example 3 and Example 1 was cycled at room temperature. After 100cls of cycling, the battery cell was discharged to 1.5V, and then the battery cell was removed and disassembled. The negative electrode sheet was soaked in DMC pure solvent for 10 minutes, then cut into a 2mm*4mm rectangle, and glued to the sample table with conductive glue. EDS test was performed using a HITACHI (SU8100) scanning electron microscope to characterize the dissolution of positive electrode Mn ions. Test results are shown in Figure 1 and Figure 2 ,in Figure 1 The test results for comparative example 3 are as follows: Figure 2 This is the test result of Example 1.

[0133] from Figure 1 and Figure 2 It can be seen from the comparison that in lithium-ion batteries without silicon nitrile additives and trithiophosphite additives, after 100 cycles of the battery, a large amount of Mn ions in the positive electrode are dissolved and reduced at the negative electrode, destroying the SEI film and hindering Li + The migration of Mn leads to increased polarization of the negative electrode and accelerated capacity decay. However, in lithium-ion batteries with silicon nitrile additives and trithiophosphite additives, only a small amount of Mn was detected on the negative electrode side, indicating that the combined use of the two types of additives can significantly inhibit the dissolution of positive electrode metal ions, prevent the deposition of positive electrode oxidation products on the negative electrode, and slow down the occurrence of side reactions at the electrode / electrolyte interface, thereby ensuring the long cycle life of lithium batteries.

[0134] The present invention also carried out the above test on other proportions, and the results were basically the same. Due to limited space, they are not listed one by one.

[0135] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. An electrolyte additive, characterized in that: The additives include a silicon nitrile compound shown in structural formula I and a trithiophosphite compound shown in structural formula II; Wherein, R is selected from at least one of trimethylsilyl, trimethylsilyloxy, C1-C10 unsubstituted or substituted alkyl, alkoxy, C2-C10 unsubstituted or substituted alkenyl, C2-C10 unsubstituted or substituted alkynyl, and C6-C10 unsubstituted or substituted aryl; R1 to R6 are independently selected from at least one of trimethylsilyl, trimethylsilyloxy, C1 to C10 unsubstituted or substituted alkyl or alkoxy, C2 to C10 unsubstituted or substituted alkenyl, C2 to C10 unsubstituted or substituted alkynyl, C6-C10 unsubstituted or substituted aryl, hydrogen, halogen, cyano, isocyanate, and isothiocyanate.

2. An electrolyte additive according to claim 1, characterized in that: R is at least one of C1-C10 unsubstituted or substituted alkyl, alkoxy, and C2-C10 unsubstituted or substituted alkenyl, and R1-R6 are independently selected from at least one of C1-C10 unsubstituted or substituted alkyl, isocyanate, and trimethylsilyl.

3. An electrolyte additive according to claim 1 or 2, characterized in that: The structural formula I is selected from at least one of structural formulas I-1 to I-3:

4. An electrolyte additive according to claim 1 or 2, characterized in that: The structural formula II is selected from at least one of structural formulas II-1 to II-3:

5. A non-aqueous electrolyte, characterized in that: The electrolyte additive comprises the electrolyte additive according to any one of claims 1 to 4.

6. A non-aqueous electrolyte according to claim 5, characterized in that: The non-aqueous electrolyte also includes an organic solvent, a lithium salt and conventional additives.

7. A non-aqueous electrolyte according to claim 6, characterized in that: The total mass of the electrolyte additive and the conventional additive is 5-20% of the total mass of the non-aqueous electrolyte.

8. A non-aqueous electrolyte according to claim 5 or 6, characterized in that: The mass of the silicon nitrile compound is 0.2-3% of the total mass of the non-aqueous electrolyte, and the mass of the trithiophosphite compound is 0.2-5% of the total mass of the non-aqueous electrolyte.

9. A lithium ion battery, characterized in that: The non-aqueous electrolyte comprises the non-aqueous electrolyte according to any one of claims 5 to 8.

10. A lithium ion battery according to claim 9, characterized in that: The lithium-ion battery further comprises a positive electrode, a negative electrode and a separator, and the active material in the positive electrode is a lithium-rich manganese-based active material.